2015
DOI: 10.1007/s00198-015-3163-5
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of spinal alignment and quality of life after corrective surgery for spinal kyphosis in patients with osteoporosis: a comparative study with non-operated patients

Abstract: This study evaluated changes in spinal alignment and quality of life (QOL) after corrective spinal surgery for patients with postmenopausal osteoporosis and spinal kyphosis. Spinal global alignment and QOL were significantly improved after corrective spinal surgery but did not reach the level of non-operated controls. Introduction With the increased aging of society, the demand for corrective spinal instrumentation for spinal kyphosis in osteoporotic patients is increasing. However, previous studies have not f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Typically, one or more thoracolumbar vertebrae sustains an anterior wedge deformity as the anterior region of the vertebral body collapses (Ismail et al, 1999). In severe cases, the entire spine develops a senile kyphosis which can be painful and disabling (Francis et al, 2008;Miyakoshi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, one or more thoracolumbar vertebrae sustains an anterior wedge deformity as the anterior region of the vertebral body collapses (Ismail et al, 1999). In severe cases, the entire spine develops a senile kyphosis which can be painful and disabling (Francis et al, 2008;Miyakoshi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also, patients with the apex at a caudal level seemed to have less self-esteem issues with increasing magnitude of the kyphotic deformity [22]. Quality of life including physical functioning improved after corrective spinal surgery in adult patients with a symptomatic thoracolumbar or lumbar kyphosis secondary to osteoporosis [23]. Patients with Scheuermann kyphosis showed that functional outcome significantly improved 2 to 8 years after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…13 There has been an increasing recognition of importance of sagittal balance and parameters because sagittal balance has been found to be significantly associated with patients' health-related quality of life (HRQOL). 4,14 Patients with low back pain and lumbar degenerative diseases are characterized by the loss of LL and the increase of PT, which may lead to severe sagittal imbalance that is analyzed as a result of the interaction of regional deformities and compensatory mechanisms to present as deformity patterns if these compensatory mechanisms do not manage to compensate for original deformities. 15,16 The compensatory mechanisms can occur in spine, pelvis, and/or lower limb areas and the mean objective is to extend the adjacent segments of the kyphotic spine to rebalance the axis of gravity, including: reduction of TK that can be observed in flexible spines, hyperextension of adjacent segments which can also limit the lumbar kyphosis to restore the sagittal balance, retrolisthesis, pelvis retroversion (increase of PT and rotation of the pelvis), knee flexion, and ankle extension.…”
Section: Discussionmentioning
confidence: 99%